SISTEM REKOMENDASI BUTIK OSHKOSH B’GOSH CIPUTRA SEMARANG MENGGUNAKAN FRAMEWORK CODEIGNITER (Information Technology and Telematics, 2015)
Abstrak— Oshkosh B'Gosh boutique Ciputra Semarang is a boutique that has various types of collections are very numerous, but does not have a system that can recommend products. On this basis, the research conducted with the aim to build a system to enable the equitable distribution of recommendations marketing products owned. Recommendations are given done by calculating the similarity between the related product information. Similarity calculation method used in this study is the cosine similarity. There are some steps being taken that tokenizing, filtering, stopword, stemming hereinafter cosine similarity calculation that would be obtained values ranging from 0 to 1. If the calculation results obtained closer to the value 1, it can be said to have a close resemblance, but if the result of calculation has a value of 0, the resemblance is less appropriate. The results of the calculation will be represented by similarity ranking. In addition to using the Cosine Similarity this system using CodeIgniter framework. Keywords: System recommendations Cosine similarity, tokenizing, filtering, stopword, Stemming, CodeIgniter